2021
DOI: 10.1038/s41525-021-00196-7
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 gain-of-function heterozygous cell models reveal diverse interferon-signature gene transcriptional responses

Abstract: Signal transducer and activator of transcription 1 (STAT1) gain-of-function (GOF) is an autosomal dominant immune disorder marked by wide infectious predisposition, autoimmunity, vascular disease, and malignancy. Its molecular hallmark, elevated phospho-STAT1 (pSTAT1) following interferon (IFN) stimulation, is seen consistently in all patients and may not fully account for the broad phenotypic spectrum associated with this disorder. While over 100 mutations have been implicated in STAT1 GOF, genotype–phenotype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Although common in this patient population, neither patient here had evidence of current or past CMC, which may be attributed to the early identification of STAT1 GOF mutations, as well as timely prophylaxis. The IFN response of STAT1 GOF patients and distinct mutations can be heterogeneous and may reflect multifactorial transcriptional and biological regulation (48,49). The development of HLH is an infrequent manifestation of STAT1 GOF mutations (50).…”
Section: Discussionmentioning
confidence: 99%
“…Although common in this patient population, neither patient here had evidence of current or past CMC, which may be attributed to the early identification of STAT1 GOF mutations, as well as timely prophylaxis. The IFN response of STAT1 GOF patients and distinct mutations can be heterogeneous and may reflect multifactorial transcriptional and biological regulation (48,49). The development of HLH is an infrequent manifestation of STAT1 GOF mutations (50).…”
Section: Discussionmentioning
confidence: 99%
“…This increased disease severity caused by DBD mutations may be explained in part by prolonged nuclear presence and possibly DNA binding of STAT1, as recently demonstrated in cell models by our group and others. 11,12 Importantly, however, the above in vitro studies identified kinetic and transcriptional differences even among DBD mutations, suggesting that our understanding of the functional impact of such mutations remains incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the genotype‐phenotype correlation in STAT1 GOF has remained elusive. While mutations in all STAT1 domains have been shown to result in the molecular hallmark of enhanced tyrosine‐701 phosphorylation, 9 the mechanisms leading to this GOF phenomenon may vary among different mutations 11‐15 . For instance, mutations in the DBD have been shown to result in enhanced nuclear accumulation, reduced nuclear mobility, and slower dephosphorylation of STAT1 in vitro in STAT1 GOF cell models 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations